Patients with HBV‐related acute‐on‐chronic liver failure have increased concentrations of extracellular histones aggravating cellular damage and systemic inflammation. Issue 1 (23rd September 2016) - Li, X.; Gou, C.; Yao, L.; Lei, Z.; Gu, T.; Ren, F.; Wen, T.
Abstract: Acute‐on‐chronic liver failure (ACLF) is the most common type of liver failure and associated with grave consequences. Systemic inflammation has been linked to its pathogenesis and outcome, but the identifiable triggers are absent. Recently, extracellular histones, especially H4, have been recognized as important mediators of cell damage in various inflammatory conditions. This study aimed to investigate whether extracellular histones have clinical implications in patients with hepatitis B virus (HBV)‐related ACLF. One hundred and twelve patients with HBV‐related ACLF, 90 patients with chronic hepatitis B, 88 patients with HBV‐related liver cirrhosis and 40 healthy volunteers were entered into this study. Plasma histone H4 levels, cytokine profile and clinical data were obtained. Besides, patient's sera were incubated overnight with human L02 hepatocytes or monocytic U937 cells in the presence or absence of antihistone H4 antibody, and cellular damage and cytokine production were evaluated. We found that plasma histone H4 levels were greatly increased in patients with ACLF as compared with chronic hepatitis B, liver cirrhosis and healthy control subjects and were significantly associated with disease severity, systemic inflammation and outcome. Notably, ACLF patients' sera incubation decreased cultured L02 cell integrity and induced profound cytokine production in the supernatant of U937 cells. Antihistone H4 antibody treatment abrogated these adverse effects, thus confirming a cause‐effect relationship between extracellular histones and organ injury/dysfunction. The data support the hypothesis that the increased extracellular histone levels in ACLF patients may aggravate disease severity by inducing cellular injury and systemic inflammation. Histone‐targeted therapies may have potentially interventional value in clinical practice.